Characterization of groundrolls in the North-West of Niger Delta Nigeria, West Africa - S.A. Ugwu; C.N. Nwankwo; J.O. Sule (Egyptian Journal of Petroleum)
A study of the character and dispersion patterns of groundrolls during seismic survey in the North – West of Niger Delta was undertaken in order to provide information and data for its suppression. Eighty – three raw monitor records were analysed for their frequency, velocity and wavelength characteristics. The results showed that the predominant phase velocities ranged from 278 to 726 m/s with a mean of 376 m/s, the frequency values were 5.3 to 14.1 Hz with a mean of 6.5 Hz. The results showed that the groundrolls in this area were dispersive and this is consistent with the theory of groundrolls in nature and velocity layering and non – homogenous nature of the Niger Delta. Vistal – 12 processing software was also used to carry out F–K analysis on the raw monitor records with groundrolls and the output showed clear monitor record without groundroll. The groundrolls could be suppressed by keeping the geophones arrays and source patterns at distances of not less than 10 m and 70 m respectively instead of 5 m and 50 m used in the survey. Keywords: Groundrolls, Seismic survey, Dispersion, Velocity, Niger Delta